Importin β Can Bind Hepatitis B Virus Core Protein and Empty Core-Like Particles and Induce Structural Changes. - Chao Chen; Joseph Che-Yen Wang; Elizabeth E Pierson; David Z Keifer; Mildred Delaleau; Lara Gallucci; Christian Cazenave; Michael Kann; Martin F Jarrold; Adam Zlotnick (PLoS Pathogens)
Hepatitis B virus (HBV) capsids are found in many forms: immature single-stranded RNA-filled cores, single-stranded DNA-filled replication intermediates, mature cores with relaxed circular double-stranded DNA, and empty capsids. A capsid, the protein shell of the core, is a complex of 240 copies of core protein. Mature cores are transported to the nucleus by a complex that includes both importin α and importin β (Impα and Impβ), which bind to the core protein's C-terminal domains (CTDs). Here we have investigated the interactions of HBV core protein with importins in vitro. Strikingly, empty capsids and free core protein can bind Impβ without Impα. Cryo-EM image reconstructions show that the CTDs, which are located inside the capsid, can extrude through the capsid to be bound by Impβ. Impβ density localized on the capsid exterior near the quasi-sixfold vertices, suggested a maximum of 30 Impβ per capsid. However, examination of complexes using single molecule charge-detection mass spectrometry indicate that some complexes include over 90 Impβ molecules. Cryo-EM of capsids incubated with excess Impβ shows a population of damaged particles and a population of "dark" particles with internal density, suggesting that Impβ is effectively swallowed by the capsids, which implies that the capsids transiently open and close and can be destabilized by Impβ. Though the in vitro complexes with great excess of Impβ are not biological, these results have implications for trafficking of empty capsids and free core protein; activities that affect the basis of chronic HBV infection.